TINGKAT PERANAN PEMBELAJARAN KIMIA DALAM MENDUKUNG GERAKAN SEKOLAH SEHAT, AMAN, RAMAH ANAK, DANMENYENANGKAN (STUDI KASUS) - Yusran Khery; Pahriah Pahriah; Hasinarmi Hasinarmi (Universitas Pendidikan Mandalika Mataram, 2016)
This study aimed to determine the level of learning the role of chemistry in supporting a healthy school movement, a safe, child-friendly, and fun (a case study in SMAN3 Mataram). This study used qualitative design to find out how the learning process chemistry students in the school to support the movement of healthy, safe, child friendly, fun environment SMAN3 Mataram. Subject of research was teachers and students learning chemistry class III. The instrument used in this study was the observation of the environment of the school and the learning process, interviews with teachers to find out the learning process in learning chemistry related to school environment healthy, safe, child friendly and pleasant and the student questionnaire to determine the level of the role of chemistry learning in support of the movement schools healthy, safe, child friendly, and fun during the process of chemical learning. The results of the study was indicate that the rate of learning the role of chemistry in supporting a healthy school movement, a safe, child-friendly, and fun can improve student learning SMAN 3 Mataram.